Analysis of the influence of brand performance, perceived quality, and brand experience on brand loyalty with brand satisfaction as an intervening variable at Fore Coffee in Solo Raya - Aprilia, Natasya Eka; Moechammad Nasir (Jurnal Mantik, 2025)
This study examines the influence of Brand Performance, Perceived Quality, and Brand Experience on Brand Loyalty, with Brand Satisfaction acting as an intervening variable at Fore Coffee in the Solo Raya region. A quantitative approach was used, collecting primary data from 200 respondents via purposive sampling, focusing on customers from Klaten, Sukoharjo, and Surakarta. Data was collected using Likert-scale questionnaires, addressing variables such as brand performance, perceived quality, and customer experiences. Partial Least Square (PLS) analysis via SmartPLS v4.0 was conducted to assess the relationships between the variables. The results indicate that Brand Performance, Perceived Quality, and Brand Experience positively affect Brand Satisfaction, while Brand Satisfaction influences Brand Loyalty. However, Brand Performance and Perceived Quality do not directly influence Brand Loyalty. Brand Satisfaction mediates the relationship between these factors and Brand Loyalty. The study's limitations include a small sample size and time constraints, and future research should expand the sample size. Recommendations for Fore Coffee include focusing on enhancing product quality, customer service, and creating positive experiences to strengthen customer loyalty